Interpreting Judean Pillar Figurines: gender and empire in Judean apotropaic ritual - Darby, Erin (Forschungen zum Alten Testament / 2, 2014)
Judean Pillar Figurines regularly appear in discussions about Israelite religion, monotheism, and female practice. Erin Darby uses Near Eastern texts, iconography, the Hebrew Bible, and the archeology of Jerusalem to explore figurine function, the gender of figurine users, and the relationship between Judean figurines and the Assyrian Empire